Establishing the availability of the sigmodontine binomem Geoxus lafkenche (Rodentia, Supramyomorpha, Cricetidae) - Teta, Pablo; Dâ€™Elía, Guillermo (THERYA, 2020)
The sigmodontine species name Geoxus lafkenche proposed by Teta and Dâ€™Elía (2016) is unavailable, given that the publication where it originally appears did not satisfy the requirements of the International Code of Zoological Nomenclature. In this note we establish the availability of the species name Geoxus lafkenche, by fulfilling those requirements.